(untitled) (Simbiótica. Revista Eletrônica, 2024)
This text addresses orchestras as a cultural asset, focusing especially on the role and significance of community orchestras in collective music teaching. Such groups focus on social integration and strengthening identity through musical language, based on social phenomena triggered by the promotion of cultural and educational experiences. The discussion is an excerpt from ongoing doctoral research and covers the state of activation of this heritage. The objective is to articulate applications of knowledge from the field of heritage education, in processes and practices of public policies for culture and citizenship whose bases are orchestras. After a brief introduction to the context, a preliminary discussion and considerations on the information collected so far are presented.